Determinan Leverage dan Capital Intensity Terhadap Tax Avoidance Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Menggunakan Moderated Regression Analysis - Fazri, Fanisyah; Hariani, Swarmilah; Mindana, Eliong Jose (Journal of Economics and Management, 2024)
This study aims to examine the effect of Leverage and Capital Intensity on Tax Avoidance with Company Size as a moderation variable. The population in this study is primary consumer goods sector companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The sampling method in this study used purposive sampling techniques and obtained 215 samples of observation data. The data used is secondary data where financial statements are obtained from the official IDX website and the web of each company. The analysis method carried out is a multiple linear regression model with the help of the SPSS program version 25. The results of this study show that leverage does not have a significant effect on tax avoidance, capital intensity has a positive and significant effect on tax avoidance. The size of the company is not able to moderate the effect of leverage and capital intensity on tax avoidance